1970
DOI: 10.1037/h0029941
|View full text |Cite
|
Sign up to set email alerts
|

Eye elevation and visual space in monocular regard.

Abstract: liighly junior high school studenls made monocular comparisons of standard and variable apertures through collimating lenses in a dark room. Placement of paired targets was varied in a vertical arc with 10 combinations of elevations at 10°, 30°, 50°, 70°, and 90° to the horizontal. When the standard was the lower target, size and distance discriminations were both distorted (p < .001) in a comparable illusory direction (lower target seen as larger and nearer). No illusion was obtained for size or distance disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…He showed that the eye position shift affected perceived size and distance in binocular vision, in such a way, that, when the gaze was shifted towards the zenith, stimuli were being perceived as smaller and further. Also, the effect of the eye position shift was larger on perceived distance than on perceived size (Thor et al, 1970). All these findings show the importance of the kinesthetic information from eye muscles for perceived size and the Moon illusion.…”
mentioning
confidence: 61%
“…He showed that the eye position shift affected perceived size and distance in binocular vision, in such a way, that, when the gaze was shifted towards the zenith, stimuli were being perceived as smaller and further. Also, the effect of the eye position shift was larger on perceived distance than on perceived size (Thor et al, 1970). All these findings show the importance of the kinesthetic information from eye muscles for perceived size and the Moon illusion.…”
mentioning
confidence: 61%
“…Even with large stimulus distances, which increase the size illusion (Schur, 1926; van de Geer & Zwaan, 1964), it became not even approximately as large as the normal moon illusion. Although Kaufman and Rock (1962) rejected a potential role for the angle of regard in the normal moon illusion, the size illusion under darkroom conditions or homogeneous-field conditions appears to be a fairly stable although small phenomenon (Baird, Gulick, & Smith; Hermans, 1954; Leibowitz & Hartmann, 1959; Thor, Winters, & Hoats, 1969, 1970).…”
Section: Angle Of Regard and Apparent Sizementioning
confidence: 97%
“…There are at least two more objections to the more specific vergence-effort hypothesis. First, the size illusion has been found when the target stimuli were in monocular view (e.g., Schur, 1926; Thor et al, 1970), although it was also found to be smaller than with binocular view (van de Geer & Zwaan, 1964). When targets are viewed monocularly, vergence effort should play no role.…”
Section: Angle Of Regard and Apparent Sizementioning
confidence: 99%
“…In many experiments on the effect of eye elevation on apparent size, only negligible or limited effects were reported. Most of them, however, were conducted only under monocular viewing conditions (e.g., Gruber, King, & Link, 1963; Hermans, 1954; Thor, Winters, & Hoats, 1970). If they had adopted binocular ones, a larger effect of eye elevation would have been observed.…”
Section: Angle Of Regard Reconciled With Binocular Viewingmentioning
confidence: 99%